Republic of Equatorial Guinea : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Director for the Republic of Equatorial Guinea. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2016)
This 2016 Article IV Consultation highlights that Equatorial Guinea's overall real GDP growth has been weak in recent years averaging -0.5 percent from 2010-14, largely owing to a trend decline of the dominant hydrocarbon sector. Economic performance deteriorated substantially in the wake of the 2014 oil-price shock. In 2015, the pace of the contraction intensified, and economic activity declined by 7.4 percent. The near-term outlook is very challenging, given prospects for depressed energy prices and a continued decline in hydrocarbon production. Weak oil revenues and limited buffers will require further cuts to public investment, leading to a deep contraction of the large construction sector and public administration.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet